Death and Afterlife - Davis, Stephen T. author. aut Link
XI, 211 p.
Keywords: This book began as a series of papers at a conference called "Death and Afterlife" held in Claremont, California in January, 1987 under the auspices of the Department of Religion of the Claremont Graduate School. The responses to each paper and several comments are also included.